Functionally graded ceramics (FGC) dental abutment with implant-supported cantilever crown: Finite element analysis. (February 2023) - Ouldyerou, Abdelhak; Merdji, Ali; Aminallah, Laid; Mehboob, Hassan; Mehboob, Ali; Roy, Sandipan; Goswami, Tarun; Mukdadi, Osama M.; Tarlochan, Faris
Abstract: The design factor of the dental abutment may affect the stability of the implant. Therefore, choosing the right abutment is required for the patient's long-term therapy. The aim of this study is to examine the impact of different abutment materials on the biomechanical behavior of dental implants, abutments and bone tissues using finite-element analysis. For dental abutment, four materials were chosen: titanium, zirconia, and axial functionally graded ceramics (FGM1 and FGM2). The FGM1 was designed with alumina ceramic in the upper section and zirconia at the bottom section, whereas the FGM2 was designed with zirconia in the upper section and alumina at the bottom section. An axial and an oblique load of 100 N were applied separately on the occlusal face of the cantilever crown. As a result, the FGM2 abutment exhibited the highest stress response, whereas titanium showed the lowest stress levels in the abutment. On the contrary, FGM1 and FGM2 showed less stress on the implant. Further, stress was greater under oblique loading compared to axial loading. Functionally graded ceramic composites for dental abutments may enhance the stability of the implant more than metal abutments. Graphical abstract: Image 1 Highlights: FGM2 with higher stiffness on the abutment base outperformed in terms of reducing stress in the implant. Stresses generated on the bone were not affected by the abutment material. The biomechanical performance of the alumina-zirconia composite abutment strongly suggests that it is a preferable material to titanium abutment.